Research on Evaluation Index System of Urban Energy Internet Development. Issue 2 (February 2020) - Zhao, Zhiqiang; Li, Haifeng; Wang, Xiaochen; Li, Zhuonan; Yu, Zhiyong; Zhang, Zengqiang; Song, Xinfu
Abstract: At present, urban energy development faces problems such as energy resources shortage, low utilization efficiency and serious environmental pollution. The urban energy Internet is considered to be an effective means to solve urban problems. In order to effectively evaluate the development of urban energy Internet, this paper has established a detailed evaluation index system from four aspects: clean and low carbon, safe and efficient, flexible and intelligent, and open sharing of urban energy development, and given some data of foreign developed countries. reference. The evaluation indicator system can be used as a pre-guided and evaluation indicator for urban energy Internet development planning.